Bullying by peers in childhood and effects on psychopathology, suicidality, and criminality in adulthood. (October 2015) - Klomek, Anat Brunstein; Sourander, Andre; Elonheimo, Henrik
Summary Bullying is shown to be associated with adverse outcomes in cross-sectional studies, but only a few studies have prospectively examined the effects of childhood bullying on adult outcomes. Our Series paper focuses on prospective longitudinal studies that used large, population-based, community samples analysed through quantitative methods and published between 1960 and 2015. We describe the results of childhood bullying in adulthood in three of the most burdensome areas: psychopathology, suicidality, and criminality. We note that the different groups involved (ie, victims, bullies, and bully–victims) are at risk of difficulties later in life, but their risk profiles differ and the contributions are probably not independent. Controlling for confounders reduces the risk and sometimes eliminates it. Victims are at a high risk of internalising disorders. Bullies seem to be at risk of later externalising disorders and criminality, mainly violent crime and illicit drug misuse. Bully–victims seem to be at risk of internalising disorders, externalising disorders, and criminality, but not all studies examined bully–victims as a separate group. Boys and girls differ in their long-term outcomes. A dose effect exists in which frequent bullying involvement in childhood is most strongly associated with adult adversities. Future studies need to control for additional factors (including genetic, psychosocial, and environmental) to account for the mechanisms behind the reported longitudinal associations.